(untitled) (Research, Society and Development, 2023)
Squamous cell carcinoma (SCC) is a malignant epithelial neoplasm derived from keratinocytes, commonly preceded by actinic (solar) keratosis, with unclear etiology but associated with host and environmental factors. The present study aimed to describe the therapeutic association of surgical resection with electrochemotherapy using carboplatin in a case of SCC. The work was conducted using qualitative methodology, providing a detailed case report of a domestic feline treated at a private hospital unit. The cat was of mixed breed, female, spayed, 12 years and 4 months old, with white and gray fur, weighing 5.1 kg. The patient presented with a unilateral ulcerative lesion on the lower right eyelid, which had been evolving for 2 years with a significant increase in size and ulceration for approximately 3 months. After an incisional biopsy for histopathological examination, the diagnosis of SCC was confirmed, and it was decided to perform surgical excision with 2 cm margins, along with two sessions of carboplatin electrochemotherapy. After 40 days from the second electrochemotherapy session, with no signs of recurrence, the patient was discharged.